Explanations for the Current Crisis in Venezuela - Ellner, Steve (2019)
Five explanations have been proposed from different political standpoints to explain the root cause of the “humanitarian crisis” in Venezuela: 1.- the unrelenting hostility of internal and external adversaries, leading to international sanctions and threats of military action; 2.- the plummeting of international oil prices, aggravated by the government’s failure to diversify production and sever dependency on petroleum; 3.- mistaken policies that discouraged private investments; 4.- the mismanagement and incompetence of the Maduro government; and 5.- socialism’s inherent contradictions and unsustainability. In this essay, the author examines each explanation and argues that in order to explain the crisis in Venezuela it is necessary to understand the interrelation and context of the four initial explanations. As they are complementary to each other.